Menakar Tantangan Brigade Pangan dalam Mewujudkan Swasembada Pangan : Studi Kasus di Kabupaten Sidrap, Sulawesi Selatan - Muhammad Arsyad; Andi Amran Sulaiman; Andi Nuddin; Muhammad Hatta Jamil; Abd. Haris Bahrun; Jamaluddin Al Afgani (Jurnal Penyuluhan Pertanian, 2025)
Learning from the New Order era (1970–1984), when Indonesia successfully achieved rice self-sufficiency through the Green Revolution and earned an FAO award, the government launched the Food Brigade Movement in 2023 to involve the younger generation in accelerating national food self-sufficiency. By mid-2025, the program had demonstrated notable progress in attracting young farmers to contribute to agricultural and economic development. As with any large-scale movement built within a relatively short period, several institutional aspects still require strengthening, particularly cross-sector coordination and synergy among related institutions.This research, conducted in Sidrap Regency, aims to identify and map the challenges faced by the Food Brigade in achieving food self-sufficiency. Using an expert survey and the Interpretative Structural Modeling (ISM) approach, twenty sub-elements were analyzed, and eleven were identified as key challenges. The ISM results reveal that five challenges fall into the independent sector, while six are positioned in the linkage category.The main challenges relate to policy and governance systems, including: (1) The mechanism for drafting and implementing Memorandum of Understanding (MoU) for land management still needs to be strengthened; (2) cross-sectoral coordination is not yet fully integrated; (3) some Food Brigade establishment processes still require alignment with the technical guidelines; and (4) policy and program harmonization among relevant agencies still needs to be improved